A Study of Conceptual Understanding, Science Process Skills, and Representational Coordination through Guided Inquiry with Integrated Physical and Virtual Laboratories - Theo Jhoni Hartanto; Pri Ariadi Cahya Dinata; Suhartono Suhartono (Universitas Pendidikan Mandalika, 2026)
This study examines changes in prospective physics teachers’ conceptual understanding, science process skills, and representational coordination in light refraction learning following a guided inquiry design integrating real and virtual laboratories. The study employed a one-group pretest–posttest design with a concurrent embedded mixed-methods approach involving 15 prospective physics teacher students. Quantitative data were analyzed using the Wilcoxon signed-rank test and N-gain analysis, while qualitative data were examined through representational coordination coding, including visual-graphical, symbolic-mathematical, and verbal-textual representations. The results showed an increase in students’ conceptual understanding, with average scores rising from 10.07 on the pretest to 21.80 on the posttest, as indicated by the Wilcoxon test result (p < 0.05). he average N-gain score of 0.79 falls within the high category of improvement. Science process skills also increased from 3.93 to 8.33 (p < 0.001), with an average N-gain of 0.73, which falls within the high category. Qualitative findings indicated a shift from predominantly verbal and fragmented explanations toward more varied representations and relatively more coherent conceptual structures. Overall, the findings suggest that the integration of real and virtual laboratories within guided inquiry was associated with changes in conceptual understanding, science process skills, and representational coordination among prospective physics teachers.